Narratives of Play and Creativity: Preschool Teachers’ and Children’s Experiences in Fostering Fine Motor Creativity through Play-Based Learning - Nunung Nuryati; Nelia Guswanti; Deden HMS; Elnawati Elnawati (Yayasan Adra Karima Hubbi, 2026)
Background. Early childhood represents a critical period for the development of cognitive, emotional, social, and motor skills, with play serving as an essential context for learning and self-expression. Understanding the factors that contribute to children’s creativity, particularly fine motor creativity, is important for supporting holistic development in early childhood education.Purpose. This study aimed to examine the simultaneous contribution of playfulness, cognitive flexibility, emotional regulation, and social interaction to fine motor creativity in preschool children.Method. A correlational research design was employed with a sample of 120 children aged 4–6 years from several early childhood education centers. Standardized instruments and observational assessments were used to measure playfulness, cognitive flexibility, emotional regulation, social interaction, and fine motor creativity. The data were analyzed using Pearson correlation and multiple regression to determine both individual and combined effects of the predictor variables.Results. The findings indicated that playfulness, cognitive flexibility, emotional regulation, and social interaction were all significantly and positively associated with fine motor creativity. Multiple regression analysis revealed that these variables collectively explained 62% of the variance in fine motor creativity, with playfulness showing the strongest individual contribution.Conclusion. The results suggest that fine motor creativity develops through the integration of cognitive, emotional, and social processes rather than through isolated factors. These findings highlight the importance of play-based learning environments that promote imaginative engagement, flexible thinking, emotional regulation, and cooperative interaction. The study provides practical implications for early childhood educators, curriculum developers, and parents in designing holistic approaches that support creativity and motor skill development.